2015
DOI: 10.3324/haematol.2014.112755
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric study underlining the interest of adding CD5, CD7 and CD56 expression assessment to the flow cytometric Ogata score in myelodysplastic syndromes and myelodysplastic/myeloproliferative neoplasms

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 26 publications
6
32
1
Order By: Relevance
“…We believe that setting up the “Ogata score” is technically easy, time‐ and cost‐efficient, making it suitable for general use in LA laboratories. Additionally, its reproducibility has already been demonstrated by different groups …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We believe that setting up the “Ogata score” is technically easy, time‐ and cost‐efficient, making it suitable for general use in LA laboratories. Additionally, its reproducibility has already been demonstrated by different groups …”
Section: Discussionmentioning
confidence: 80%
“…Hence, many research groups are working on its improvement. Bardet et al have reported that the addition of two new variables (CD7 aberrant expression on myeloid progenitors and CD56 on monocytes) improve the score sensitivity. Recently, Ogata et al have also reported that adding the CD33 expression on CD34+ cells as a fifth parameter (called granulocyte/CD34 cell CD33 ratio) to the classic four parameters improves it sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the four-parameter diagnostic score, Bardet and colleagues advised the addition of CD7 (on myeloid progenitors) and CD56 (on monocytes) to the diagnostic score. 28 Specificity of this adjusted score was 87%; however, the sensitivity was low (66%). Here, the addition of selected erythroid markers might improve the sensitivity of FC.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the sensitivity of this and other scoring systems is highest for the high-risk groups. 18…”
Section: Limitations Of This Studymentioning
confidence: 99%